Effects of probiotics Lacticaseibacillus paracasei and Bacillus amyloliquefaciens on water quality and inhibition of Vibrio vulnificus and Vibrio alginolyticus in white shrimp (Litopenaeus vannamei) culture - Kanmanee Sukkasem; S. Thiankham; K. Srisomwong; Pramod K. Kantha; S. Kitikiew (International Journal of Agricultural Technology, 2025)
The infected white shrimp (Litopenaeus vannamei) caused by Vibrio alginolyticus and Vibrio vulnificus pose significant threats to white shrimp farming. Using probiotics for disease prevention and water quality improvement offers a promising eco-friendly alternative as it avoids chemical residues. This study evaluated the effectiveness of a probiotic formulation containing Lacticaseibacillus paracasei and Bacillus amyloliquefaciens at a concentration of 106 CFU/g. The probiotics were applied at concentrations of 0.125 and 0.1875 mL/L. White shrimp (average weight of 6 grams) were stocked at a density of one shrimp per liter for 15 days. Results demonstrated that ammonia levels were significantly lower in the treatments with probiotics compared to the control treatment. However, nitrite levels were elevated in the treatment. The probiotics did not affect temperature, pH, dissolved oxygen and total alkalinity. Notably, the probiotic treatment effectively reduced Vibrio spp. in the system with bacterial counts markedly lower in treatment compared to the control. The survival rates of white shrimp following a challenge with Vibrio spp. were 90% and 96.67% for the treatments with 0.125 mL/L and 0.1875 mL/L of probiotics while the control treatment exhibited 0% survival by day 13. The probiotic treatments also enhanced the immune response of white shrimp by increased total hemocyte count and clearance efficiency. Thus, probiotics can effectively reduce Vibrio spp. and ammonia levels while improving white shrimp survival even under infectious conditions.
Keywords: Aquaculture disease management and microbiota; Aquaculture Nutrition and Growth; Aquatic life and conservation